Hubungan Inisiasi Menyusu Dini dan ASI Eksklusif dengan Stunting pada Baduta Usia 7-24 Bulan - Annisa, Nur; Sumiaty, Sumiaty; Tondong, Henrietta Imelda (Poltekkes Kemenkes Palu, 2019)
The prevalence of stunting in five-year-old infants in Indonesia in 2018 it is 30.8% while in two-year babies it is 29.9% which consists of 12.8% very short and 17.1% short. Stunting can be caused by a variety of factors, such as the implementation of initiation of early breastfeeding which is not appropriate and the provision of breast milk is not exclusive. The purpose of this study is to know the relationship between early breastfeeding initiation and exclusive breastfeeding with stunting in two-year-old infants aged 7-24 months in the work area of Pantoloan Health Center. This type of research is an analytical survey with design cross sectional. The sample in this study were two-year-old infants aged 7-24 months totaling 57 samples with sampling techniques namely simple random sampling and data analysis using Chi Square. The results showed that respondents who experienced stunting were 36.8% and not stunting 63.2%. Respondents who had early breastfeeding initiation tended not to experience stunting (79.2%), while respondents who received exclusive breastfeeding tended not to experience stunting (81.0%). The results of the statistical test showed a significant relationship between early breastfeeding initiation and exclusive breastfeeding with stunting with the same p-value of 0.033 (? <0.05). The conclusion is that there is a relationship between early breastfeeding initiation and exclusive breastfeeding with stunting. Suggestions for researchers for health workers to promote and implement early breastfeeding initiatives and exclusive breastfeeding for mothers to prevent and minimize the incidence of stunting in children in the future.